Evaluation of grain yield potential of oat germplasm in Bulgaria - Panayotova, Galina (MTT, 2004)
During the last years the interest in oats as a multipurpose crop suitable to production of food and feed grains, forage and bedding for animals increases in Bulgaria. The Institute of Agriculture and Seed Science Obraztcov chiflik , Ruse develops and releases improved spring and winter oat varieties for the farmers and the food industry (Panayotova 2004). The objective of this research was to record the progress obtained in the oat breeding program and to evaluate grain yield potential of elite Bulgarian oat germplasm. Oat grain yield is strongly influenced by environmental conditions One of the main objective of oat breeding program is using method of recurrent selection as an effective breeding procedure to produce improved oat germplasm with higher grain yield potential (Holland et al. 2002; Stuthman et al. 1992). A recurrent selection program for adaptation to diverse environments was successful in improving mean oat (Avena sativa L.) grain yield within and across testing environments. Sixty three oat genotypes, result of our program were evaluated from 2000- 2003 for his grain yield at the field of the Institute of Agriculture and Seed Science Obrazcov chiflik , Ruse (43° 48 N latitude, 26° 02 E longitude) in a randomized complete block with three replications. A number of traits have been evaluated for possible correlated responses. Significant positive correlations were found between grain yield, 1000 seeds mass and seed number. The best ten lines, regardless of their yield potential were used as parents in diallel combinations without reciprocals: p (p-1)/2. Promising yield grain potential was demonstrated in some of cultivars and breeding lines of oat breeding program in Bulgaria. 1000 seeds mass and seed number. The best ten lines, regardless of their yield potential were used as parents in diallel combinations without reciprocals: p (p-1)/2. Promising yield grain potential was demonstrated in some of cultivars and breeding lines of oat breeding program in Bulgaria. Holland, J.B. et al. 2002. Euphytica 126: 265 274; Panayotova, G. 2004. Proc. of 39 Croatian Symposium on Agriculture Opatija Croatia 1: 251-252; Stuthman, D.D. et al. 1992. Proc. of 4th Intern. Oat Conference Adelaide, South Australia 1: 70-76
Keywords: Ka; oat; grain; yield